2009
DOI: 10.1203/pdr.0b013e318189487e
|View full text |Cite
|
Sign up to set email alerts
|

Lung and Systemic Inflammation in Preterm Lambs on Continuous Positive Airway Pressure or Conventional Ventilation

Abstract: Intratracheal lipopolysaccharide (LPS) causes acute inflammation and injurious mechanical ventilation results in pulmonary and systemic inflammation. We aimed to determine in preterm lungs if continuous positive airway pressure (CPAP) protects against pulmonary and systemic inflammation, compared with conventional mechanical ventilation (CMV) after intratracheal LPS. Preterm fetuses were exposed to maternal betamethasone and Epostane 36 h before delivery at 133 d gestational age (term ϭ 150 d). Lambs were intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 39 publications
4
71
0
Order By: Relevance
“…As compared with unventilated fetal controls, the ventilated groups had increased mRNA expression of early response markers of lung injury (CTGF, CYR61, and EGR1) (16) as well as IL-1β and IL-6, noted previously as indicators of volutrauma in our preterm lamb model (17)(18)(19). Similarly, BAL inflammatory cells, EGR1, and MPO protein expression in the tissue were increased in CV and VV animals as compared with fetal controls, although lung tissue injury scores did not differ.…”
Section: Effect Of Ventilation Pattern On Inflammation and Lung Injurymentioning
confidence: 63%
“…As compared with unventilated fetal controls, the ventilated groups had increased mRNA expression of early response markers of lung injury (CTGF, CYR61, and EGR1) (16) as well as IL-1β and IL-6, noted previously as indicators of volutrauma in our preterm lamb model (17)(18)(19). Similarly, BAL inflammatory cells, EGR1, and MPO protein expression in the tissue were increased in CV and VV animals as compared with fetal controls, although lung tissue injury scores did not differ.…”
Section: Effect Of Ventilation Pattern On Inflammation and Lung Injurymentioning
confidence: 63%
“…All lambs received prophylactic surfactant (100 mg/kg, Curosurf; Chiesi Farmaceutici) at 15 min. Lambs were subsequently ventilated in volume guarantee mode with a VT of 7 ml/kg, which is the normal VT for lambs at this gestation (44). Throughout ventilation, lambs were sedated by continuous infusion of Alfaxane (3 mg·kg Ϫ1 ·min Ϫ1 ) through an umbilical vein catheter implanted immediately after delivery.…”
Section: Methodsmentioning
confidence: 99%
“…The initiation of mechanical ventilation of the preterm lung, irrespective of how it is conducted, produces lung inflammation and injury (10,44,60). The key proinflammatory cytokines initiated by ventilation are IL-1␤, IL-6, and IL-8.…”
Section: Effect Of Iugr On Fetal Lung Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of mechanical ventilation associated with the initiation of ventilation on fetal lungs with chronic ureaplasma infection are unknown. Our previous studies with acute exposures to lipopolysaccharide (LPS) showed an amplification of inflammation with ventilation (18). However, chronic fetal proinflammatory exposures may result in a tolerance phenomenon with suppressed inflammation (19).…”
mentioning
confidence: 99%